Exploring multicultural narratives in 1000 library grant book: A focus on West Java context - Opik Opik; Dadang Sunendar; Vismaia Sabariah Damayanti; Bunyamin Maftuh; Dayu Rifanto (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2025)
Indonesia, as a multicultural country with a wide diversity of cultures, religions, and ethnicities, emphasizes the importance of promoting inclusivity and preserving local identity through education. This study aims to evaluate the suitability of multicultural themes and representations of West Javanese cultural contexts in 1,000 books donated by the National Library to 10,000 community reading parks in 2024. This study is a qualitative descriptive study using the content analysis method. The population in this study was books obtained from Librarians at the National Library, while the sample was selected using a purposive sampling technique, which came from 1000 books with a multicultural context and representation of the West Java cultural context. Data collection techniques include observation, interviews, and documentation. Data analysis techniques were carried out using content analysis. The results showed that 35.19% of the books evaluated discussed multicultural themes. This theme was more common at the intermediate and advanced reader levels (B3 and C) than at the beginner level (A). Books specifically themed around West Java only represented 4.81% of the collection, highlighting the limitations of local cultural narratives. This study concludes that there is great potential to strengthen regional identity, foster pride in cultural heritage, and provide insight into traditional values through the provision of books on cultural heritage.